Risk Management in Finance and Logistics - Xu, Chunhui (Translational Systems Sciences, 2018)
This is the first book to introduce the major quantitative tools in risk management taking financial investments and logistics planning as the background: optimization and stochastic programming. Contained here are the fundamentals of portfolio selection theory from the point of view of risk control, and methods for risk control with new and popular risk measures such as VaR (Value-at-Risk) and CVaR (Conditional VaR). The book also introduces a new theory for risk management in more general investment situations such as flexible investment decisions, providing an accessible and comprehensive introduction to the interrelations between these fields of research. Basic concepts of stochastic programming are introduced, and their applications to risk management in inventory distribution and network design are covered as well. Illustrated by carefully chosen examples and supported by extensive data analyses, this book is highly recommended to readers who seek an in-depth and up-to-date integrated overview of the ever-expanding theoretical and quantitative fields of risk management in financial investment and logistics planning.